George P. Moschis tribute special issue: His philosophy and contributions. Issue 4 (2nd October 2019) - Mathur, Anil
ABSTRACT: In this article, I first discuss Moschis' contributions to marketing in three main areas of consumer behavior: consumer socialization, older consumer behavior, and life course research. Next, I present and comment on the basic characteristics of his work: multi-theoretical, programmatic, and collaborative. Finally, I briefly present the gist of the contribution that is made by each of the articles included in the first part of this two-part special issue that have as foundation his work in the area of life course research.